H3M - A Network Access Methodology Supporting QoS - Foudriat, E. C.; Maly, K.; Li, Y. (Computing and Informatics, 2012)
This paper presents a physical and media access layer methodology that is able to significantly improve quality of service (QoS) performance. Since QoS relates to a wide range of features, access protocols supporting it must be multifaceted. This paper presents the H3M (Heterogeneous, Hierarchical, Highly Mobile) network system which supports QOS. First, H3M uses an improved access paradign --- DMNA (Dynamic Multiple Node Access), i.e., nodes decide the manner in which they submit data during their access period. Multiple implies both many nodes interacting and each node submitting all its pending information. Multiple also implies that during an access frame, different access mechanisms are provided for both synchronous and asynchronous message-traffic types. Using DMNA, dynamic recovery of unneeded capacity is made possible and recovered capacity is made available to other nodes and subframes immediately. For example, a voice call in silent phase immediately adjusts to its capacity needs without signaling. This provides an improved level of QoS support over single access, fixed-frame, fixed-slot size technology. H3M access was originally targeted to WLAN (Wireless Local Area Networks); it provides mechanisms for multiple clustering. Intra-clustering uses techniques where all nodes share a band; inter-clustering where clusters are able to communicate across the whole network by using the heterogeneous characteristics that nodes will have differing equipment. Communication across the network is enabled with minimal routing, with predictable delays, with simple multicasting, etc., features which greatly enhance the QoS in H3M. H3M features variable frequency, variable bandwidth (VFVB) channeling base upon Digital Software Radio technology. It enables each cluster to adapt its capacity needs to its present loading. The combination of DMNA to dynamically share bandwidth within a frame and VFVB sharing between frames provides support for load balancing to minimize congestion problems again supporting superior QoS. H3M was originally [17--19] proposed and is still applicable for wired ad hoc local (LAN) and metropolitan (MAN) area networks. Hence, it is able to support Enterprise Networks (EPN), i.e., private shared link networks used by companies, universities, etc., presently using IEEE 802.X technology. With modification, it is applicable to point-to-multipoint networks such as ground-satellite links and mobile telephony. Further, because of H3M versatile nature, it can operate as a bridge-type network with minimal adjustment to packets transferred through and into for bridging between interfaces networks using standard ATM and IEEE protocols. The paper documents H3M performance by simulation at the cluster level. It supports loads ranging up to 80% of capacity and wide variation between synchronous and asynchronous traffic. Synchronous traffic performance is constant throughout the load range; asynchronous traffic shares the remaining effective bandwidth for both large and small message sizes is with no evidence of choking.